ALIMENTAÇÃO, COMIDA E CULTURA: O EXERCÍCIO DA COMENSALIDADE - Romilda de Souza Lima; José Ambrósio Ferreira Neto; Rita de Cássia Pereira Farias (Universidade do Estado do Rio de Janeiro, 2015)
This article, presented as an essay, brings forward a conceptualreflection on food and culture. In this context, part of thediscussion is geared towards commensality and its importancethroughout the historical and social process involved in theformation of different peoples, presenting use of fire as a majorcultural and social factor that promoted the integration, as wellas the core piece for the change of eating habits. The dynamicsof commensality, dietary habits in the contemporary era and itsconnections with the traditional and the modern. This debatealso brings forward the approaches used by some authors onthe anthropology and sociology of food, the difference betweennourishment and food - when it comes to physiological andautomatic aspects, such as a support for human survival and themeaning given by the cultural bias - when eating also acquires asymbolic importance. Therefore, this article is based on a culturaland social understanding of food. It is that sense in which,through socially established rules, bonds between the eater andother dynamics involving commensality are created. DOI: 10.12957/demetra.2015.16072